Perutusan Naib Canselor 2016:APEX 2020 Merealisasikan Universsiti Global. - Osman, Omar (2016)
“Refer to universities who have mission transcending the boundaries of the nation-state; taking the global perspective and advancing the frontiers of knowledge worldwide.This includes intensified cross-border mobility of students and increased international collaboration of research and scholarly work.”